Enhanced Greedy Perimeter Forwarding Algorithm for Mobile Sensor Network in Cluster region - Hemalatha, S; George Dharma Prakash Raj, E (International Journal of Computer Sciences and Engineering, 2019)
In mobile wireless networks, path breakage happens frequently due to the movement of mobile nodes, node failure, channel fading and shadowing. It is challenging to combat path breakage at the cost of minimum control overhead, while adapting to topological changes rapidly. We propose a new greedy technique EPFA (Enhanced Perimeter Forwarding Algorithm) for transmitting the mobile nodes from source to destination. The nodes will be communicated and travelled properly by the new technique without a greater loss. Moreover the paper discuss about the cluster or region head, the role of the CH and the subordinate TH node. The algorithm clearly explains about the work flow of the CH and TH. The simulation diagram discusses about the packet delivery ration, collision rate, total delay of the node in the required time and the energy consumption rate of the mobility node.